Surgically Treated Nonunion following Ischial Tuberosity Avulsion Fracture of a 14-Year-Old Athlete - Yuta Nakamatsu; Tomoaki Fukui; Keisuke Oe; Shinya Hayashi; Tomoyuki Matsumoto; Takehiko Matsushita; Ryosuke Kuroda; Takahiro Niikura (Case Reports in Orthopedics)
A 14-year-old girl experienced acute left buttock pain during a sprint. At the local hospital, she was diagnosed with an avulsion fracture of the left ischial tuberosity. She was kept for observation for about 10 months; however, the buttock pain persisted, and the bone fragments did not unite. She was referred to our hospital approximately 11 months after the injury. Plain radiography revealed an increased transposition of the bone fragment, from 12 mm immediately after the injury to 23 mm. Twelve months after the injury, she underwent osteosynthesis using two cannulated cancellous screws and three suture anchors. Following postoperative rehabilitation, the power in her left hamstring recovered, and she was able to run at full speed and returned to athletics 9 months after the surgery. The operative indications for avulsion fractures of the ischial tuberosity are unclear. Careful follow-up is required as the rate of nonunion after conservative treatment tends to be high. This needs to be identified in order to provide timely treatment that allows for early return to sport. Although she had significant chronic pain and muscle weakness, the surgery successfully treated the fracture, and her muscle power recovered, leading to her return to sports.